2010
DOI: 10.2147/jaa.s10839
|View full text |Cite
|
Sign up to set email alerts
|

Fluticasone furoate nasal spray: Profile of an enhanced-affinity corticosteroid in treatment of seasonal allergic rhinitis

Abstract: Of the classes of pharmacotherapy for seasonal allergic rhinitis, intranasal corticosteroids are the preferred treatment and are recommended in practice guidelines as first-line pharmacotherapy for rhinitis with prominent nasal congestion. The enhanced-affinity intranasal corticosteroid fluticasone furoate nasal spray (GW685698X), is one of the newest additions to the armamentarium for allergic rhinitis. This review summarizes the preclinical and clinical data on fluticasone furoate nasal spray and discusses i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 49 publications
1
8
0
2
Order By: Relevance
“…different INCS are characterized by different pharmacological and pharmacokinetic properties [8]. It is reported that fluticasone furoate has the highest relative glucocorticoid receptor affinity and lipophilicity, an extensive hepatic first-pass metabolism, and with one of the lowest systemic exposures and potential risks among INCS used for AR [3,8].…”
Section: The Pharmacokinetics Of Fluticasone Furoate Given Intranasalmentioning
confidence: 99%
See 3 more Smart Citations
“…different INCS are characterized by different pharmacological and pharmacokinetic properties [8]. It is reported that fluticasone furoate has the highest relative glucocorticoid receptor affinity and lipophilicity, an extensive hepatic first-pass metabolism, and with one of the lowest systemic exposures and potential risks among INCS used for AR [3,8].…”
Section: The Pharmacokinetics Of Fluticasone Furoate Given Intranasalmentioning
confidence: 99%
“…It exhibits its antiinflammatory effect as an entire molecule and is therefore not a prodrug or a salt [2]. The exact mechanism of action of fluticasone furoate in treating AR is not full known, and may affect the early and late phase inflammatory response [3]. It is suggested that being a corticosteroid, it exhibits its anti-inflammatory effect on multiple inflammatory cells (such as, mast cells, eosinophils, neutrophils, macrophages, and lymphocytes) and mediators (such as, histamine, eicosanoids, leukotrienes, and cytokines) [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Efektivitas terapi steroid topikal ini adalah 67% dibandingkan dengan terapi plasebo 39%. 5 Terapi operatif sendiri menurut WHO ARIA dilakukan setelah terapi medikamentosa gagal, 2 namun terjadinya kongesti hidung, baik karena proses remodelling yang bersifat ireversibel atau proses inflamasi yang menimbulkan edema, dapat membatasi penetrasi steroid topikal ke mukosa rongga hidung. 6,7 Terapi reduksi konka merupakan salah satu operasi pada RA.…”
Section: World Health Organization-allergy and Itsunclassified